"I forgive myself": The association between self‐criticism, self‐acceptance, and PTSD in women victims of IPV, and the buffering role of self‐efficacy. Issue 2 (14th October 2020) - Crapolicchio, Eleonora; Vezzali, Loris; Regalia, Camillo
Abstract: The effects of intimate partner violence (IPV) concerning specifically posttraumatic stress disorder (PTSD) symptomatology have been widely demonstrated, but the consequences of abuse are not the same for all victims. We know little about the psychological processes that limit these adverse consequences. Therefore, we explored the association between self‐criticism felt by abused women and their PTSD, and we investigated self‐acceptance as the underlying process explaining this relationship. We also examined self‐efficacy as the protective (moderating) factor. The results indicated that self‐criticism was indirectly associated with greater PTSD via lower self‐acceptance. Critically, the indirect effect only emerged for individuals low in self‐efficacy.